1976
DOI: 10.1002/1097-0142(197609)38:3<1323::aid-cncr2820380335>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Primary mucinous adenocarcinoma of thyroid gland

Abstract: A mucin-producing carcinoma in the thyroid gland found in a 44-year-old man was first thought to be a metastatic carcinoma, possibly from salivary gland. However, follow-up examinations for 8 years have not demonstrated another neoplasm, and it seems reasonable to conclude that this lesion was a rare primary mucinous adenocarcinoma of the thyroid gland.Cancer 38:1323-1325, 1976.RIMARY MUCIN-PRODUCING ADENOCARCINOMA P of t h e thyroid gland is very rare, if not unreported, i n the literature. A review of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…Primary mucinous carcinomas of the thyroid gland are extremely rare. Since the first report published by Diaz et al in 1976, only 6 such case reports were identified during our search of the PubMed database [3–8]. Furthermore, primary mucinous carcinoma of the thyroid gland with rhabdoid cells has never been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Primary mucinous carcinomas of the thyroid gland are extremely rare. Since the first report published by Diaz et al in 1976, only 6 such case reports were identified during our search of the PubMed database [3–8]. Furthermore, primary mucinous carcinoma of the thyroid gland with rhabdoid cells has never been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…These tumours do not represent a true primary thyroid mucinous carcinoma. In fact, this latter is extremely rare (only four cases reported), and histologically, it is indistinguishable from a mucinous carcinoma at other sites [3,5,7,9]. In these case, areas of papillary or follicular carcinoma are not always evident.…”
Section: Discussionmentioning
confidence: 99%
“…This latter is exceptionally rare, with only six cases reported in literature, and histologically are indistinguishable from mucinous carcinoma of others sites [3,5,7,9]. We describe two cases of a mucinous tumour of the thyroid where one is a primary carcinoma as demonstrated by immunohistochemistry and the second represents a first clinical manifestation of a mucinous carcinoma of the ovary.…”
Section: Introductionmentioning
confidence: 92%
“…[5][6][7][8][9][10] In 1991, Chan et al Pathologically, SMECE is characterized by sclerosis, mucin, and squamous features with eosinophilic infiltrate surrounded by desmoplastic stroma. 4,[11][12][13][14][15][16][17] It is often associated with Hashimoto's thyroiditis.…”
Section: Introductionmentioning
confidence: 99%